DINAMIKA KEMISKINAN DAN STRATEGI PENGENTASAN KEMISKINAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI BANTEN TAHUN 2023 - Kyla Rahma; Siti Nurfatimah; Ishma Nur Syafira; Intan Nuraini; Deris Desmawan (LPPM Universitas Ekasakti, 2024)
The Human Development Index (HDI) serves as a comparative tool for assessing life expectancy, education, and living standards. It illustrates the extent to which the population has access to developmental outcomes such as income, health, and education. However, issues such as poverty persist even in regions like Banten. Indeed, poverty represents a significant and distressing social issue prevalent across various regions, including Provinsi Banten. This research aims to evaluate the 2023 poverty rates within Provinsi Banten, utilizing a blend of primary and secondary sources for data acquisition. Descriptive and correlation analyses serve as the methodologies employed in this study. The key variables investigated include Kemiskinan, Pengentasan Kemiskinan, and the human development index. It has been observed from the findings that the human development index significantly influences Kemiskinan in Provinsi Banten.